The paradigm of integral ecology and the epistemological foundations of Van Potter's global bioethics - Giacobello, Maria Laura (Medicina e Morale, 2021)
The current epochal crisis has seriously damaged the environment. Among the voices raised to protect the "Common Home", that of the Church also emerges through Pope Francis. Using the expression "integral ecology", he makes explicit reference to the awareness that in reality everything is connected. Starting with Nature's cry of rebellion, integral ecology thus undertakes the onus of calling for a radical renewal, of ordinary ethical categories as well as of the anthropological and gnoseological ones at the heart of the prevailing western culture, based on the mechanistic paradigm. Within the broad framework of a rethinking of the traditional boundaries of ethics, integral ecology can represent an alternative cultural paradigm, a real expression of the spirit of the time. In this regard, it is particularly interesting and fruitful to reflect on the extraordinary convergence between the perspective of integral ecology and that of Van Potter's global bioethics: in fact, the American scientist had laid the epistemological foundations for a different ethical vision already in the 1970s. The idea of a systemic approach aimed at enhancing the relationship the individual parts have with each other and with the whole, although generated by evidently different assumptions, unequivocally unites the two perspectives. In fact, Potter's reflection starts from the same awareness located at the basis of integral ecology, that of man's deep rootedness in the ecosystem: through the assumption of a systemic vision and the concept of bio-cybernetics, the scientist offers a valid representation of the interactive character of the structural organization that presides over the workings of the natural environment.